Impact of tooth wear on masticatory performance. (September 2018) - Sterenborg, Bernadette A.M.M.; Kalaykova, Stanimira I.; Loomans, Bas A.C.; Huysmans, Marie-Charlotte D.N.J.M.
Abstract: Objective: Masticatory performance is influenced by a number of variables such as age, gender, bite force, and occlusal units. Tooth wear may also play a role due to changes in occlusal area and in vertical dimension of occlusion. The aim of this study was to evaluate the effect of tooth wear on masticatory performance, using a communition test. Materials and Methods: Patients with different degrees of tooth wear, referred by their general dental practitioners, and included in the Radboud Tooth Wear Project, were approached for this study and included after informed consent. The amount of post canine wear was scored with the Tooth Wear Index (TWI). The number of occluding posterior units was quantified and the bite force was measured using a transducer. Masticatory performance was measured with a communition test, with the median particle size (X50) after 20 chewing cycles as outcome measure. A multiple regression model was used to assess the relation between TWI, age, gender, bite force, occlusal units and X50. Results: 52 participants (40 male, 12 female, mean age: 40 ± 8.2y) were included in the study. The post canine TWI-score was between 1.0-3.3. The average number of occlusal units per participant was 11.9 ± 1.4 and the mean bite force 369 ± 172 N. The mean X50 was 4.2 ± 1.1. The results showed no significant relation between post canine TWI-score, age, gender, bite force, and occlusal units upon the X50 (p > 0.13). Conclusion: This study showed that the degree of tooth wear could not be observed to have an effect on masticatory performance. Clinical significance: On individual level an effect could be present but looking at a larger group of patients, the degree of tooth wear did not have a relation with masticatory performance as measured with a communition test.